Anti Diabetic effect of CL 316,243 (A β3-Adrenergic Agonist) by Down Regulation of Tumour Necrosis Factor (TNF-α) Expression - Ghorbani, Masoud; Shafiee Ardestani, Mehdi; Gigloo, Sedigheh Hatami; Cohan, Reza Ahangari; Inanlou, Davoud Nouri; Ghorbani, Peyman (PLOS ONE, 2012)
Objective Obesity is a risk factor for the development of insulin resistance and is one of the most important contributors to the pathogenesis of type2 diabetes, which acts mainly through the secretion of adipokines such as TNF-α that may influence insulin sensitivity. TNF-α affects many aspects of adipocyte function, such as adipocyte development and lipid metabolism. Material and Methods We demonstrated that there is a correlation between the expressions of TNF-α in retroperitoneal WAT and insulin-resistance in 8 genetically obese fa/fa rats. Treatment of animals with CL 316,243, a β3-adrenergic agonist, showed an improvement of insulin-resistance that was linked with the suppression of TNF-α mRNA expression in WAT. Results These results confirm the association between TNF-α expression and the insulin-resistant condition in rats. Our finding indicates that the hyperglycaemia and hyperinsulinemia induced by insulin-resistance correlated positively with the expression of TNF-α mRNA in an abdominal WAT depot. Conclusion We conclude that CL 316,243 possesses both anti-diabetic effects and anti-obesity effects in rodents.